English speaking migrant children in educational and cultural transition. - Macdonald, Winifred L. (Curtin University, 1998)
The purpose of the research was to investigate whether cultural dissonance was experienced by a group of migrant students during educational and cultural transition to new education systems which shared cultural markers of language and ethnicity. Cultural dissonance is defined in this study as:A sense of discord or disharmony, experienced by participants in cultural change where cultural differences are found to occur which are unexpected, unexplained and therefore difficult to negotiate and which inhibit behavioural adaptation.The study utilised case histories of children from forty-seven families. The respondents in the research were the children's parents. The families had emigrated from the United Kingdom to Western Australia during the period 1985-1995.The families reported receiving little information about education systems in Western Australia prior to migration. In the post-migration period, little official information was provided at system or at school level. Because placing the children in schools was a priority for the families, encounters with Western Australian education systems took place within a few weeks of their arrival as migrants.This lack of prior information meant that cultural differences in educational provision were unexpected and unexplained. In particular, families encountered unexpected problems in the appropriate placement of their children in Western Australian schools. Accented English and differences in word usage led to unexpected rejection and teasing. The perceived failure on the part of schools to address these and other differences caused confrontations between parents and many schools and disrupted the children's educational progress. These discordant experiences and difficulties led to what, in this study, is characterised as cultural dissonance.The implications for the study are discussed on two levels. With particular reference to Western Australian education systems, the lack of induction policies for English-speaking migrant children was apparent. There appeared to be no system or school level guidelines which mandated the use of printed matter, provided at State system level to address these difficulties. The schools were not seen to make good use of the information parents provided about the children's educational stages. The intervention of teachers at classroom level to discourage teasing was seen as ineffective and in two cases teachers contributed to the problems being encountered.On a more general level, the study has implications for attitudinal change within Australian society towards the reception of skilled and financially secure migrant new criteria for entry to Australia have implications for the socio-economic status of potential migrants. The self-identity of these families is influenced by their status in the social hierarchies of their country-of origin. Skilled and professional families are likely to resist policies for their children's induction being seen as a low priority in Western Australian schools simply because of the child's migrant status.The research findings gave rise to recommendations that:Information of education systems in Western Australia should be made available to all intending migrant families with children.Induction policies for all migrant children should be in place and be utilised in Western Australian schools.The formulation of policy takes account of the effects of changes to migrant socio- economic status, brought about by the changes to the criteria for entry to Australia.The study concluded that shared markers of language and ethnicity were not sufficient to ensure that the cultural differences in education systems were not experienced by the families. A lack of prior information on those differences and a lack of induction policies for the children led to difficulties and to experiences of cultural dissonance for the families.